Gene-activated dermal equivalents to accelerate healing of diabetic chronic wounds by regulating inflammation and promoting angiogenesis - Lou, Dong; Luo, Yu; Pang, Qian; Tan, Wei-Qiang; Ma, Lie (Bioactive materials, 2020)
Diabetic chronic wound, characterized by prolonged inflammation and impaired angiogenesis, has become one of the most serious challenges in clinic and pose a significant healthcare burden worldwide. Although a great variety of wound dressings have been developed, few of encouraged achievements were obtained so far. In this study, the gene-activated strategy was applied to enhance sustained expression of vascular endothelial growth factor (VEGF) and achieve better healing outcomes by regulating inflammation and promoting angiogenesis. The gene-activated bilayer dermal equivalents (Ga-BDEs), which has good biocompatibility, were fabricated by loading the nano-sized complexes of Lipofectamine 2000/plasmid DNA-encoding VEGF into a collagen-chitosan scaffold/silicone membrane bilayer dermal equivalent. The DNA complexes were released in a sustained manner and showed the effective transfection capacities to up-regulate the expression of VEGF in vitro. To overcome cutaneous contraction of rodents and mimic the wound healing mechanisms of the human, a reformative rat model of full-thickness diabetic chronic wound was adopted. Under the treatment of Ga-BDEs, speeding wound healing was observed, which is accompanied by the accelerated infiltration and phenotype shift of macrophages and enhanced angiogenesis in early and late healing phases, respectively. These proved that Ga-BDEs possess the functions of immunomodulation and pro-angiogenesis simultaneously. Subsequently, the better regeneration outcomes, including deposition of oriented collagen and fast reepithelialization, were achieved. All these results indicated that, being different from traditional pro-angiogenic concept, the up-regulated expression of VEGF by Ga-BDEs in a sustained manner shows versatile potentials for promoting the healing of diabetic chronic wounds. [Display omitted] •Gene-activated strategy overcomes short half-life period of growth factors.•Releasing DNA complexes in sustained manner and effective transfection capacities.•Without cutaneous contraction, reformative full-thickness diabetes chronic wound.•VEGF versatile potentials: immunoregulation, pro-angiogenesis in different phases.•One intervenor covered two main pathogenic factors: inflammation and angiogenesis.